Pabrikasi Sabun Padat dari Minyak Jelantah Sebagai Penyelesaian Permasalahan Limbah di Sekolah - Hidayah, Wahyudi; Hidayah, Ridho; Mutiara, Yolanda (Yayasan Daarul Huda Kruengmane, 2024)
Food and life are inseparable in the living world. Humans today consume millions of different kinds of fatty foods. Despite its many uses, oil is currently a major source of environmental issues. Disposing of spent cooking oil waste continuously without taking the environment into account can have detrimental effects on both the environment and the ability of humans to survive. So, in order to reduce household waste—especially that which has the potential to harm the environment—innovation must be introduced to society. It is possible to turn used cooking oil waste from fried food vendors or domestic frying pans back into soap. This program attempts to increase public awareness of environmental issues while offering instruction and support in soap-making techniques.